Nucleotide sequence of the glpD gene encoding aerobic sn-glycerol 3-phosphate dehydrogenase of Escherichia coli K-12. - Austin, D (1991)
Aerobic sn-glycerol 3-phosphate dehydrogenase, encoded by the glpD gene of Escherichia coli, is a cytoplasmic membrane-associated respiratory enzyme. The nucleotide sequence of glpD was determined. An open reading frame of 501 codons was preceded by a consensus Shine-Dalgarno sequence. The proposed translational start and reading frame of glpD were confirmed by determining the nucleotide sequence across the fusion joint of a glpD-lacZ translational fusion. The predicted molecular weight, 56,750, corresponds well with the reported value of 58,000 for purified sn-glycerol 3-phosphate dehydrogenase. The flavin-binding domain, located at the amino terminus, was identified by comparison with the amino acid sequences of other flavoproteins from E. coli. Repetitive extragenic palindromic sequences were identified downstream of the glpD coding region. The site for transcription termination was located between 87 and 216 bp downstream of the translation stop codon.